Pengaruh Aplikasi Kompos Gulma Siam Chromolaena odorata terhadap Produksi Senyawa Metabolit Sekunder sebagai Ketahanan Tanaman pada Tanaman Cabai - Vira Kusuma Dewi; Nugroho Susetya Putra; Benito Purwanto; Santika Sari; Sri Hartati; Lilian Rizkie (Fakultas Pertanian Universitas Padjadjaran, 2019)
Chromolaena odorata (L.) is a organic material as potential compost and botanical pesticides since it compounds have the potential as a pesticides is secondary metabolite. The aim of this research was to know the effects of siam weed Chromolaena odorata compost on production of secondary metabolites in the chili. The experiment was arranged in complete randomized design consisted of four treatments (no fertilizer, cow manure, siam weed compost and inorganic fertilizers) and four replications. The research was done by comparing the chemical content of leaves analyzed by Gas Chromatography-Mass Spectrometry (GC-MS) and phytochemical test. This study was conducted from September 2010 to Februari 2011, in the green house of Departement Plant Pest & Diseases, Faculty of Agriculture. In order to the extraction and characterization of secondary metabolites was conducted at the Laboratory of Chemistry, Universitas Gadjah Mada. Overall, the results of study showed that C. odorata compost could give positive effect on production of secondary metabolites as follow terpenoid, alkaloid, steroid and flavonoid on chili